Does the risk of poor mental health rise before widowhood? - Feng, Zhiqiang; Dibben, Chris; Everington, Dawn; Williamson, Lee; Raab, Gillian (International Journal of Population Data Science, 2019)
Background A large body of literature has shown that transition into widowhood has detrimental effects on the surviving spouse’s health leading to elevated risks of mortality, poor mental health and hospitalisation. However, few studies have examined health outcomes before widowhood. Anticipatory grief and long term care giving are likely to lead to poor mental health conditions. Aim This paper examined whether the risk of depression and anxiety rose before the widowhood event using linked administrative data. Methods The study population was drawn from the Scottish Longitudinal Study (SLS) linked to prescribing data, available from 2009. We included all cohort members who were married in 2001 and who were aged 50 and over by 2009. We then followed the cohort for 5 years from 2009 to 2013 (N=~58,000). Andersen-Gill models were used to explore the risk of prescription of antidepressant and antianxiety drugs before and after loss of spouse adjusting for a number of confounders. The analysis was carried out separately for men and women. Results We found that the risk of depression and anxiety were higher 6 months before widowhood for women (0-3 months, HR=1.17, 95%CI 1.07-1.28; 3-6 months, HR=1.15, 95%CI 1.05-1.27) but not for men (0-3 months HR=1.07, 95% CI 0.90-1.26; 3-6 months HR=1.01, 95% CI 0.84-1.21). The risk after widowhood for men became significantly higher lasting for 2 years (0-3 months HR=1.40, 95% CI 1.21-1.61; 21-24 months HR=1.24, 95% CI 1.01-1.52). For women the elevated risk remained at a heightened level up to 2 years (0-3 months HR=1.50, 95% CI 1.29-1.75; 21-24 months HR=1.29, 95% CI 1.03-1.60). Conclusion It has been previously shown that widowhood has negative effects on a surviving partners’ health. This research shows that this effect is also apparent in women before their partner’s deaths.